Az újrealisták szépprózája: Alekszej Varlamov és Alekszandr Sznyegirjov művei alapján - Kondratyjeva, Viktorija (Studia Litteraria, 2020)
The paper calls attention to the realist tendency in contemporary Russian literature, which intensified in the past two decades, highlighting the “new realist” trend. The author also points out that the realist tendency is not homogeneous, it includes various writing methods which may differ greatly. To illustrate this the paper introduces two contemporary authors, Alexey Varlamov and Alexander Snegirev, and through their most characteristic works two realist, but markedly different writing methods: Varlamov converges his realist point of view towards an archaic-mythological aspect, Snegirev’s method is ruthlessly honest, describing the dehumanisation and superficial nature of people.